1997
DOI: 10.1001/archsurg.1997.01430280104017
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Helicobacter pylori in Patients With Surgical Peptic Ulcer

Abstract: No significant association of H pylori infection and peptic ulcer was noted between patients who required surgical treatment compared with those who required only medical treatment; H pylori played only a limited role in the cause of disease in surgical patients, perhaps only in the cases complicated with stenosis or intractable ulcers. This suggests that presently adequate acid reduction procedure will still be the main objective of surgical treatment and prevention of the ulcer recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For instance, Lee et al [10] demonstrated that the H. pylori seropositivity of patients having complications of their peptic ulcer was similar to that for patients not having complications.…”
Section: Emergency Surgery For Peptic Ulcer Diseasementioning
confidence: 99%
“…For instance, Lee et al [10] demonstrated that the H. pylori seropositivity of patients having complications of their peptic ulcer was similar to that for patients not having complications.…”
Section: Emergency Surgery For Peptic Ulcer Diseasementioning
confidence: 99%
“…We excluded 540 articles due to the following reasons: editorial ( n = 3), meta‐analysis ( n = 6), review article ( n = 22), title and abstract showed not relevant ( n = 224), duplicate ( n = 153), outlying islands of Taiwan (n = 9), in gastric cancer group ( n = 7), in group with specific diseases ( n = 36), no data of H. pylori prevalence ( n = 67), in specific age group ( n = 4), or children and adolescents ( n = 9). Subsequently, we added the unpublished data of the present study and excluded 13 ineligible articles after review of full texts and one article which there was no full‐text available for identification, and the remaining 29 clinical articles were eligible 17–44 . The information of each study including data collecting period, participants, setting, study site, mean or range of age, numbers of H. pylori positivity, numbers of study participants was shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…This study was conducted in the main island of Taiwan which was divided into four regions: Northern, Central, Southern, and Eastern regions. 13 In these 19…”
Section: The Regions Of Main Island In Taiwanmentioning
confidence: 99%
“…The true incidence of surgical emergencies is unclear at this time. The Asian literature suggests that although the incidence of operation for overall management of ulcer disease may be decreasing, the incidence of emergent operation for ulcer-related problems actually is increasing [3,4]. The literature in the US population is variably reported as to the increase [5] or decrease in need for emergent operation [6,7].…”
Section: The Problemsmentioning
confidence: 99%